Vector portals at future lepton colliders - Sagar Airen; Edward Broadberry; Gustavo Marques-Tavares; Lorenzo Ricci (Journal of High Energy Physics)
Abstract We assess the sensitivity of future lepton colliders to weakly coupled vector dark portals (aka “Z ′ bosons”) with masses ranging from tens of GeV to a few TeV. Our analysis focuses on dark photons and L μ – L τ gauge bosons. We consider both visible and invisible decay channels. We demonstrate that both high energy μ colliders and future e + e − colliders, using the FCC-ee Z-pole and ZH operation modes as a benchmark, offer significant improvements in sensitivity. We find that both colliders can enhance the sensitivity to L μ – L τ bosons (for both visible and invisible decays) and to invisibly decaying dark photons by 1–2 orders of magnitude across the relevant mass range. Furthermore, we study the impact of forward μ detectors at the μ-collider on the sensitivity to both models.